2018
DOI: 10.1016/j.ygyno.2018.05.018
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of frontline paclitaxel/carboplatin/bevacizumab, paclitaxel/carboplatin/temsirolimus, or ixabepilone/carboplatin/bevacizumab in advanced/recurrent endometrial cancer

Abstract: PFS was not significantly increased in any experimental arm compared to historical controls. NRG Oncology/Gynecologic Oncology Group Study GOG-86P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
87
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(88 citation statements)
references
References 27 publications
1
87
0
Order By: Relevance
“…Bevacizumab yielded a response rate of 14% and a 6‐month PFS rate of 40% in women who received 1 to 2 prior cytotoxic regimens for endometrial cancer, which compares favorably with any other second‐line regimen . In the randomized phase 2 GOG 86P trial, the addition of bevacizumab to front‐line carboplatin and paclitaxel therapy did not improve PFS compared with historical controls, although it did increase OS (HR, 0.71 [95% CI, 0.55‐0.91]) . Conversely, a randomized phase 2 Italian trial (MITO END‐2) reported a significant increase in PFS from 8.7 to 13 months with the addition of bevacizumab to upfront carboplatin and paclitaxel chemotherapy, although these results have not been published in full .…”
Section: Future Directionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Bevacizumab yielded a response rate of 14% and a 6‐month PFS rate of 40% in women who received 1 to 2 prior cytotoxic regimens for endometrial cancer, which compares favorably with any other second‐line regimen . In the randomized phase 2 GOG 86P trial, the addition of bevacizumab to front‐line carboplatin and paclitaxel therapy did not improve PFS compared with historical controls, although it did increase OS (HR, 0.71 [95% CI, 0.55‐0.91]) . Conversely, a randomized phase 2 Italian trial (MITO END‐2) reported a significant increase in PFS from 8.7 to 13 months with the addition of bevacizumab to upfront carboplatin and paclitaxel chemotherapy, although these results have not been published in full .…”
Section: Future Directionsmentioning
confidence: 99%
“…Median survival for metastatic/recurrent endometrial cancer is short, on the order of 12 to 15 months for women with measurable disease (Table ) . For the majority of women, initial therapy for unresectable recurrent/metastatic disease will be chemotherapy with carboplatin and paclitaxel.…”
Section: Therapy For Recurrent or Metastatic Diseasementioning
confidence: 99%
See 3 more Smart Citations